Edukasi Seks Berbasis Pendidikan Kristiani bagi Anggota Jemaat Gereja Protestan Indonesia di Papua - Ruben Rewasan (Sekolah Tinggi Teologi Torsina Surakarta, 2021)
There velations about sex are often regarded as very risky, taboo, dirty and embarrassing. Similarly, in the lives of Papuans and most indonesian Protestant church members in Papua (hereinafter written GPI Papua), this action is usually done on the basis of awareness that sex is an immoral activity and will cause new deviations, especially by teenagers. Whatever reaction arises must be realized that the problem of sex is a concrete problem,but many people can not give the appropriate answer that causes a new problem. Based on these conditions, sex education needs to be organized one of them by the church to minimize the problem of sex. In its implementation, sex education in the church must be done through the preparation of a representative educational curriculum. Sex education materials integrated in the curriculum are actual and aligned with the objectives of Christian Education. Through this paper, the author wants to write theoretical thought as a contribution of thought taking into account aspects of the context of sex education organized by the church. The direction and purpose of the church's sex education curriculum is based on the Bible and is aimed at raising awareness of learners responsible for their lives for the glory of God.